2015
DOI: 10.1371/journal.pone.0139357
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cells Stimulate Platelets and Facilitate Thrombus Formation through Platelet CLEC-2: Implications in Atherothrombosis

Abstract: The platelet receptor CLEC-2 is involved in thrombosis/hemostasis, but its ligand, podoplanin, is expressed only in advanced atherosclerotic lesions. We investigated CLEC-2 ligands in vessel walls. Recombinant CLEC-2 bound to early atherosclerotic lesions and normal arterial walls, co-localizing with vascular smooth muscle cells (VSMCs). Flow cytometry and immunocytochemistry showed that recombinant CLEC-2, but not an anti-podoplanin antibody, bound to VSMCs, suggesting that CLEC-2 ligands other than podoplani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 41 publications
1
55
0
Order By: Relevance
“…Moreover, Min Fei found that the plasma level of CLEC-2 was positively correlated with the plasma GPVI level [11]. C-type lectin-like receptor 2 was found in atherosclerotic lesions, especially in advanced atherosclerotic lesions, indicating the role of CLEC-2 in atherosclerotic lesion formation [9,10]. Atherosclerotic lesion formation is the main cause of atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Min Fei found that the plasma level of CLEC-2 was positively correlated with the plasma GPVI level [11]. C-type lectin-like receptor 2 was found in atherosclerotic lesions, especially in advanced atherosclerotic lesions, indicating the role of CLEC-2 in atherosclerotic lesion formation [9,10]. Atherosclerotic lesion formation is the main cause of atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…CLEC-2-deficient platelets resulting from both methods showed normal adhesion to collagencoated capillaries under flow conditions, but the subsequent thrombus formation was severely impaired in vitro, although platelet aggregation induced by agonists other than rhodocytin was normal [27,39]. FeCl 3 -induced thrombus formation in the artery was also inhibited in CLEC-2deficient chimeras [39,40]. These mice also showed mildly increased or mild but not significantly increased tail bleeding [10,27,39].…”
Section: Thrombus Stability Under Flow Condition (Platelet Clec-2 Andmentioning
confidence: 99%
“…However, Suzuki-Inoue et al proposed platelet activation-dependent hemophilic association of CLEC-2 under flow conditions, based on surface plasmon resonance analysis using recombinant CLEC-2, and flow cytometry analysis using CLEC-2-deficient platelets. Inoue et al showed that S100A13 is a potential CLEC-2 ligand, based on protein array, surface plasmon resonance analysis using recombinant proteins, and an adhesion assay on S100A13-coated surfaces [40]. S100A13 is expressed in the cytoplasm of vascular smooth muscle cells, and is secreted from the cytoplasm upon heat shock, serum depletion, or oxidative stress [40,43,44].…”
Section: Thrombus Stability Under Flow Condition (Platelet Clec-2 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of CLEC-2 with podoplanin, which is exposed on the surface of lymphatic endothelial cells (LECs), is crucial for the separation of blood and lymphatic systems during embryogenesis (Bertozzi et al, 2010;Suzuki-Inoue et al, 2010;Hughes et al, 2015) and for the prevention of blood-lymph mixing in high endothelial venules and lymph nodes in adult organisms (Herzog et al, 2013). Platelet CLEC-2 also contributes to the maintenance of blood vessel integrity during inflammatory conditions (Boulaftali et al, 2013;Hughes et al, 2010a;Bender et al, 2013;Gros et al, 2015;Hughes et al, 2015) and has a role in thrombus stabilization under flow conditions Inoue et al, 2015;Hughes et al, 2010). Participation of platelet CLEC-2 has been demonstrated for a set of pathophysiological processes: promotion of tumor metastasis (Kato et al, 2008;Shirai et al, 2017), liver thrombosis after Salmonella Infection (Hitchcock et al, 2015), purpura and thrombocytopenia during Kazabach-Merritt syndrome in infants (O'Rafferty et al, 2015).…”
Section: Introductionmentioning
confidence: 99%